Neutrophils drive pulmonary vascular leakage in MHV-1 infection of susceptible A/J mice - Gong, Henry H.; Worley, Matthew J.; Carver, Kyle A.; Goldstein, Daniel R.; Deng, Jane C. (Frontiers in Immunology, 2023)
Lung inflammation, neutrophil infiltration, and pulmonary vascular leakage are pathological hallmarks of acute respiratory distress syndrome (ARDS) that often complicates severe respiratory viral infections. In this study, we infected resistant C57BL/6 and susceptible A/J strains of mice with pulmonary administration of murine hepatitis virus strain 1 (MHV-1) to determine mechanisms underlying pulmonary vascular leakage in this coronavirus infection model. A/J animals displayed increased lung injury parameters, pulmonary neutrophil influx, and deficient recruitment of other leukocytes early in the infection. Moreover, under basal conditions, A/J neutrophils overexpressed primary granule protein genes for myeloperoxidase and multiple serine proteases. During infection, myeloperoxidase and elastase protein were released in the bronchoalveolar spaces at higher concentrations compared to C57BL/6 mice. In contrast, genes from other granule types were not differentially expressed between these 2 strains. To determine whether these differences underlie the increased susceptibility of A/J mice to lung injury, we found that depletion of neutrophils led to mitigation of lung injury in infected A/J mice while having no effect in the C57BL/6 mice, demonstrating that an altered neutrophil phenotype and recruitment profile is a major driver of lung immunopathology in susceptible mice. These results suggest that host susceptibility to pulmonary coronaviral infections may be governed in part by underlying differences in neutrophil phenotypes, which include mechanisms involving primary granule proteins as mediators of neutrophil-driven lung injury.